2016
DOI: 10.1139/cjas-2015-0152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a phase-feeding strategy utilizing high-lipid high-fibre byproduct pellets in diets for feedlot steers

Abstract: Two studies were conducted to evaluate the provision of high-lipid high-fibre byproduct pellets when used as a partial replacement (60% in Study 1 and 30% in Study 2; HLP) for barley grain and canola meal in finishing diets (BAR). The HLP was fed for the last 49, 98, or 147 d (HLP49, HLP98, and HLP147, respectively) in Study 1, and for the last 60 or 120 d in Study 2 (HLP60 and HLP120, respectively) or the last 60 d with additional canola oil (HLP60CO). The statistical model included the fixed effects of diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Despite the tendency for improved ruminal pH observed in the current study and that of Górka et al (2015) when using HLHFP as a partial substitute for barley grain, we observed that HLHFP reduced G:F. Therefore, reducing fermentable carbohydrates by increasing lipids and fiber from byproducts as a strategy to reduce risk for ruminal acidosis is not likely to improve G:F. Diet digestibility contributes toward efficient feed conversion, and the current study supports past research demonstrating that the use of HLHFP results in a marked decrease in apparent total tract OM digestibility compared with barley-fed cattle (Górka et al, 2015). The reasons for decreased digestibility with the HLHFP diet are not known, but it is likely that the use of oat hulls within the pellet (Thompson et al, 2000), greater ether extract content (Jenkins, 1993;Hess et al, 2008), and small particle size of ingredients (Abouheif et al, 2012) in the HLHFP or a combination of any of these factors (Joy et al, 2016) can be implicated.…”
Section: Effect Of Dietary Treatmentsupporting
confidence: 82%
See 3 more Smart Citations
“…Despite the tendency for improved ruminal pH observed in the current study and that of Górka et al (2015) when using HLHFP as a partial substitute for barley grain, we observed that HLHFP reduced G:F. Therefore, reducing fermentable carbohydrates by increasing lipids and fiber from byproducts as a strategy to reduce risk for ruminal acidosis is not likely to improve G:F. Diet digestibility contributes toward efficient feed conversion, and the current study supports past research demonstrating that the use of HLHFP results in a marked decrease in apparent total tract OM digestibility compared with barley-fed cattle (Górka et al, 2015). The reasons for decreased digestibility with the HLHFP diet are not known, but it is likely that the use of oat hulls within the pellet (Thompson et al, 2000), greater ether extract content (Jenkins, 1993;Hess et al, 2008), and small particle size of ingredients (Abouheif et al, 2012) in the HLHFP or a combination of any of these factors (Joy et al, 2016) can be implicated.…”
Section: Effect Of Dietary Treatmentsupporting
confidence: 82%
“…Dietary treatments consisted of a barley grain and canola meal-based finishing diet (control [CON]) or a diet in which 55% of the barley grain and 100% of canola meal were replaced with a highlipid, high-fiber byproduct pellet (HLHFP; Table 1). The HLHFP was formulated using byproducts from the cereal grain and oilseed sectors and was similar to that used by Górka et al (2013Górka et al ( , 2015 and Joy et al (2016). Canola meal was used in the CON diet to balance the CP concentration between treatments, and limestone was added to adjust the Ca:P ratio.…”
Section: Dietary Treatments Feeding and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that feeding high-lipid byproduct-based pellets (HLP) can be an effective alternative as a partial replacement of barley grain (Joy et al 2016), or a combination of barley grain and canola meal (Górka et al 2013(Górka et al , 2015 in diets for finishing cattle. In fact, use of HLP did not affect ADG (Górka et al 2013), increased mean ruminal pH (Górka et al 2015;Joy et al 2017), and despite reducing feed conversion efficiency Joy et al 2017), may reduce the cost of gain in finishing diets.…”
Section: Introductionmentioning
confidence: 99%